Hemoglobin level is associated with severe stroke among stroke patients in Saudi Arabia - AlHarbi, Norah; Alrasheedi, Malak Salim; Alshammari, Shouq Taleb (International Journal of Health Sciences, 2020)
Objectives. The purpose of this study was to examine the association between abnormal Hemoglobin (Hb) level and stroke severity (as assessed by NIHSS). The study furthers aimed to describe the demographic and clinical characteristics of stroke patients in the middle region of Saudi Arabia. Methods. We performed a retrospective review of all medical records of the stroke patients who were treated at a major hospital in Qassim province between 2016 and 2018. Reviewed data (n=400) included demographics, Hb level on admission, type of stroke (ischemic vs. hemorrhagic), stroke risk factors, and NIHSS scores. ANOVA test was used to assess the Univariate association between NIHSS and Hb level. Regression statistics were utilized to examine the effect of abnormal Hb level on NIHSS scores while controlling for the other study variables. Data were analyzed using SPSS. Results: Sixty-nine percent of the patients were men. More young women than men (≤39 years) had a stroke. Ischemic stroke is considerably more common than hemorrhagic stroke (a ratio of 12.7:1). ANOVA test showed that the mean score of NIHSS was significantly lower among patients with a normal Hb level. Regression showed that NIHSS scores were significantly associated with abnormal Hb level, in terms of low and high level. Conclusions. This study demonstrated further evidence of the association between abnormal Hb level NIHSS. Thus, our results emphasize the predictive importance of Hb level on identifying individuals who might be at higher risk of worse neurological outcomes after stroke. Physicians need to be cognizant of the negative effect of abnormal Hb level on the outcomes of stroke patients.